ANALISIS FAKTOR YANG MEMPENGARUHI KEPUTUSANKONSUMEN UNTUK MENGGUNAKAN JASA KERETA APIKOMUTER TUJUAN LAMONGAN- SURABAYA - ISTI FATMA, AMBAR (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
Marketing has the aim to meeting the need, desires and cunsomer expectations. Expected with studying the behavior of consumer, entrepreneur are able to know abaout the need, desire and the expectations of consumer who intended to able so that give statisfaction to consumer. This research was done for knows the factors which influence the consumer decisions to use the services of komuter’s train transportation with destination from Lamongan- Surabaya. This research use the observation, quesioner, interview, study of literature and internet acces methods. Quisioner’s method consist of 213 respondent from passanger of komuter’s train with destination from Lamongan- Surabaya. The testing is use factor analysis which a in to looking for the dominant factors. Mean while, the technic of data analysis using factor analysis. Factors had been influence the consumer (passager of komuter’s train) choose the komuter’s train with destination from Lamongan- Surabaya are comfortable, safety, price, times accurancy, services and activity. Mean while, the factor are must dominant is confortable’s factor with PTC of varians 27,127%. Keyword : factor analysis, consumer decision, komuter’s train